USE OF INDICATORS OF DYSLIPIDEMIA IN THE DIAGNOSIS OF MASKED FORMS OF ARTERIAL HYPERTENSION - Hajiyeva, Y.H. (World of Medicine and Biology, 2022)
Taking into account the prevalence of arterial hypertension, its role in the development of cardiovascular diseases and mortality, increasing the effectiveness of the treatment of this pathology remains a topical issue of modern medicine. The purpose of the study is to determine the relationship between elevated blood cholesterol levels and masked arterial hypertension. The study involved 827 people aged 19 to 71, these patients without a history of arterial hypertension were divided into 2 groups: 1) with elevated blood cholesterol levels (n=375); 2) with a normal level of cholesterol in the blood (n=186) – the control group. There were no symptoms of arterial hypertension and the main risk factors (smoking, alcohol, obesity, low physical activity). The average blood cholesterol level was 6.16±0.22 mmol/l in the first group and 4.69±0.18 mmol/l in the control group. In the first group, arterial hypertension was detected in 19 people out of 138 (mean systolic pressure 152.6±4.3 mm Hg, diastolic 97.6±3.7 mm Hg), in 14 of them the cholesterol level exceeded 7.5 mmol/l, in the control group the result was negative. Thus, the use of modern devices makes it possible to detect masked arterial hypertension and carry out appropriate preventive measures.